Mechanistic elucidation of ferroptosis and ferritinophagy: implications for advancing our understanding of arthritis - Guo, Caopei; Peng, Jiaze; Cheng, Piaotao; Yang, Chengbing; Gong, Shouhang; Zhang, Lin; Zhang, Tao; Peng, Jiachen (Frontiers in Physiology, 2024)
In recent years, the emerging phenomenon of ferroptosis has garnered significant attention as a distinctive mode of programmed cell death. Distinguished by its reliance on iron and dependence on reactive oxygen species (ROS), ferroptosis has emerged as a subject of extensive investigation. Mechanistically, this intricate process involves perturbations in iron homeostasis, dampening of system Xc- activity, morphological dynamics within mitochondria, and the onset of lipid peroxidation. Additionally, the concomitant phenomenon of ferritinophagy, the autophagic degradation of ferritin, assumes a pivotal role by facilitating the liberation of iron ions from ferritin, thereby advancing the progression of ferroptosis. This discussion thoroughly examines the detailed cell structures and basic processes behind ferroptosis and ferritinophagy. Moreover, it scrutinizes the intricate web of regulators that orchestrate these processes and examines their intricate interplay within the context of joint disorders. Against the backdrop of an annual increase in cases of osteoarthritis, rheumatoid arthritis, and gout, these narrative sheds light on the intriguing crossroads of pathophysiology by dissecting the intricate interrelationships between joint diseases, ferroptosis, and ferritinophagy. The newfound insights contribute fresh perspectives and promising therapeutic avenues, potentially revolutionizing the landscape of joint disease management.